2018
DOI: 10.1039/c8cp02371a
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical description of alkali metal closo-boranes – towards the crystal structure of MgB12H12

Abstract: Theoretical investigation of closo-boranes shows that dispersive interactions are important for such compounds. New structures of MgB12H12 are proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…[11] For the 3D crystalline Mg(B 3 H 8 ) 2 , MgB 12 H 12 , and MgB 10 H 10 intermediates, the proposed structures calculated by Zhang et al were used. [3] In the case of 3D MgB 12 H 12 , we also tested the improved structural models proposed recently by Maniadaki et al [12] but the C2/m structure reported by Zhang et al [3] was found to have lower energy at the less refined level of theory adopted for our purposes. Nevertheless, it is important to emphasize that the energy variation among the 3D polymorphs (< 0.15 eV for Mg(BH 4 ) 2 and < 0.2 eV for MgB 12 H 12 ; see Figure S2 in the Supporting Information) was found to be smaller than the variation across dimensionalities, implying qualitative conclusions about morphology-dependent stability are relatively insensitive to the choice of 3D model crystal structure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[11] For the 3D crystalline Mg(B 3 H 8 ) 2 , MgB 12 H 12 , and MgB 10 H 10 intermediates, the proposed structures calculated by Zhang et al were used. [3] In the case of 3D MgB 12 H 12 , we also tested the improved structural models proposed recently by Maniadaki et al [12] but the C2/m structure reported by Zhang et al [3] was found to have lower energy at the less refined level of theory adopted for our purposes. Nevertheless, it is important to emphasize that the energy variation among the 3D polymorphs (< 0.15 eV for Mg(BH 4 ) 2 and < 0.2 eV for MgB 12 H 12 ; see Figure S2 in the Supporting Information) was found to be smaller than the variation across dimensionalities, implying qualitative conclusions about morphology-dependent stability are relatively insensitive to the choice of 3D model crystal structure.…”
Section: Resultsmentioning
confidence: 99%
“…[3] In the case of MgB 12 H 12 , the proposed polymorphs from Ref. [12] were tested, and ultimately the C2/m structure was used because it had the lowest energy computed within PBE (rather than the more sophisticated van der Waals-corrected functionals used by the authors of Ref. [12]).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tg-Mn(B 12 H 12 ) is therefore a probable model for the long time searched structure of MgB 12 H 12 . Recent calculations predict MgB 12 H 12 .structure that is stabilized by the van der Waals attraction between aromatic closo-borane anions rather than covalent bond between the metal and B 12 H 12 [36].…”
Section: Discussionmentioning
confidence: 99%
“…Contemporaneous with work done using borohydrides inside of solvents, borohydrides in the closo-borane phases were being considered as superionic conductors for rapid ion motion through their open channel pore structures [ 12 , 23 , 24 , 25 ]. Researchers doing theoretical work began to suggest that the superionic conduction would make closo-boranes promising for solid electrolytes [ 10 , 12 , 26 ]. The reasons for this superionic conduction are described in the theory paper by Kweon et al as a flat energy landscape (with many available sites for hopping), symmetry competition that ejects the cation from particular sites, and thermal reorientation of the anions [ 12 ].…”
Section: Borohydrides As Solid-state Electrolytesmentioning
confidence: 99%